Incremental to radical ideas: paradigm-relatedness metrics for investigating ideation creativity and diversity. Issue 1 (3rd April 2019) - Silk, Eli M.; Daly, Shanna R.; Jablokow, Kathryn W.; McKilligan, Seda
Abstract: Creativity and diversity are key components of success in idea generation, but each includes many dimensions. Paradigm-relatedness is an indicator of the style of creativity and diversity that has been overlooked often in assessing ideation. The goals for this study were to synthesize the literature on paradigm-relatedness, and develop and test alternative approaches for operationalizing paradigm-relatedness in ideation. The synthesis of the literature focused on reviewing both paradigm-relatedness theoretical frameworks and methodological approaches. Then, two alternative paradigm-relatedness metric approaches— category - based and component - based —were developed. Finally, ideation data was collected and coded to evaluate the reliability, ease of use, and potential applications of each approach. The category - based approach was a more reliable and faster way to code paradigm-relatedness, and so it may be more suited for research or evaluation at scale. In contrast, the component - based approach provided more explicit information on all aspects of paradigm-relatedness, but was more challenging to code reliably and more time-consuming. The component - based approach may be more suited to guiding smaller teams or individual designers in achieving paradigm-relatedness creativity and diversity. Neither approach was found to be universally ideal, and so consideration of the trade-offs is important in deciding which is most appropriate in a given situation.